1986
DOI: 10.1182/blood.v68.6.1232.1232
|View full text |Cite
|
Sign up to set email alerts
|

Use of surface marker analysis to predict outcome of adult acute myeloblastic leukemia

Abstract: In order to investigate the clinical significance of surface antigen analysis in acute myeloblastic leukemia (AML), the blasts from 196 patients with AML were analyzed prospectively with a panel of 16 monoclonal antibodies. The antibodies were selected to identify differentiation-associated antigens of either the myeloid lineage (MY9, PM-81, AML-2–23, MY7, MCS-1, MY8, Mo1, MY1, MY4, Mo2), T cell lineage (T101, T11), B cell lineage (B1, B4) or multiple lineages [J5 (CALLA), HLA-DR]. Independent morphological re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
33
0

Year Published

1989
1989
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 183 publications
(37 citation statements)
references
References 41 publications
4
33
0
Order By: Relevance
“…In conclusion, our present study indicates that two parameters are associated with high in vitro survival of AML blasts in vitro, namely, high CD13 expression and monocytic phenotype. This extends the findings of Griffin et al (1986) who demonstrated that the presence of CD13 or CD14 on AML blasts each were associated with inferior survival in patients treated with Dau Ara-C. In this context, it is also noteworthy that observed that FAB M4 and M5 were significantly associated to high autonomous proliferation in vitro, and that Campos et al (1993) noted that high Bcl-2 expression was associated with a monocytic phenotype.…”
Section: Discussionsupporting
confidence: 82%
“…In conclusion, our present study indicates that two parameters are associated with high in vitro survival of AML blasts in vitro, namely, high CD13 expression and monocytic phenotype. This extends the findings of Griffin et al (1986) who demonstrated that the presence of CD13 or CD14 on AML blasts each were associated with inferior survival in patients treated with Dau Ara-C. In this context, it is also noteworthy that observed that FAB M4 and M5 were significantly associated to high autonomous proliferation in vitro, and that Campos et al (1993) noted that high Bcl-2 expression was associated with a monocytic phenotype.…”
Section: Discussionsupporting
confidence: 82%
“…Several studies have addressed the question of correlation between blast cell immunophenotype and FAB subtype in AML, and have arrived at conflicting conclusions (Drexler et al, 1986b; 0278-0232/90/0 10047-1 2 $06.00 0 1990 by John Wiley & Sons, Ltd. Kemnitz et al, 1987;Andreasen et al, 1986;Campos et al, 1987;San Miguel et al, 1986;Drexler and Minowada, 1986;Pessanon et al, 1984;Linch et al, 1984;Griffin et al, 1986;Van Rhenen et al, 1983). Studies relating blast cell phenotype to prognosis have been fewer, and again have yielded different results Holowiecki et al, 1986) which may be due in part to their multicentric nature.…”
Section: Introductionsupporting
confidence: 88%
“…The ideal panmyeloid marker for use in diagnostic immunophenotyping in leukemia has yet to be found and analysis still relies upon the use of multiple combinations of antibodies. This single centre study has demonstrated that blast cell immunophenotype in AML is usually CD13 and CD33 positive confirming previous studies (Messner and Griffin, 1986;Griffin et al, 1986), but more commonly is SC9 positive. This latter antigen is at present poorly defined (Hogg and Horton, 1987); our findings suggest that it merits further investigation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, LAP may have an association with prognosis and response to treatment. There are many studies looking at the prevalence of LAP in AML and their clinical usefulness (Bahia et al, 2001;Griffin et al, 1986;Macedo et al, 1995b). Most focus on aberrant expression of individual antigens like CD7, CD14 and CD56 (Del Poeta et al, 1995;Norgaard et al, 2001;Raspadori et al, 2001;Tiftik et al, 2004).…”
Section: Introductionmentioning
confidence: 99%